Nutrients Content of Polianthes tuberosa Plant Waste Fermentation with Aspergillus niger as Alternative Feed Ingredients for Ruminant - ARTHUR ABDA'U; Salsabila Rahmania Sujarwo; Usman Ali; Badat Muwakhid; Umi Kalsum (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
The purpose of this study was to analyze the nutritional content such as organic matter, crude protein, crude fat, crude fiber, and non-nitrogen extract materials from the waste of the tuberose flower (Polianthes tuberosa) that was fermented by Aspergillus niger as ruminant feed. The materials used were Aspergillus niger with the availability of inoculant 2.46 x 108 CFU/g, tuberose flower waste, water and molasses. The research method uses the experimental method consisting of 5 treatments and 4 replications. Each treatment used a different dose of Aspergillus niger inoculant, namely (P0) control without fermentation, (P1) 1 x 107 CFU/g dry matter (DM) material, (P2) 3 x 107 CFU/g (DM) material, (P3) 6 x 107 CFU/g (DM) material and (P4) 9 x 107 CFU/g (DM) material, each treatment required 200 grams of tuberose flower waste.very significant (P<0.01) effect onnutritional content Polianthes tuberosa mfermented nature. The conclusion of the study was that the administration of Aspergillus niger at a dose of 9 x 107 CFU/g (DM) material was the best dose for Polianthes tuberosa fermentation with a content of 83,87±0,69 % organic matter, 11,50±0,01% crude protein, 0,31±0,08% CF, 18,62±0,23% crude fiber dan 69,57±0,18% non-nitrogen extract materials.